Would Provision of Take Home Naloxone Kits by Emergency Medical Services be Perceived as Acceptable to People at Risk of Opioid Overdose? A Qualitative Study - Bridie Evans (Prehospital Emergency Care, 2025)
Take home naloxone kits can reduce mortality, but we know little about how they are perceived by people with lived experience of opioid use. Provision of naloxone in the community has been shown to significantly reduce mortality from opioid overdose. Currently, this is predominantly through drug treatment support services but expanding provision through other services might be effective in increasing kit take-up and mortality reduction. This study aimed to examine participants' experiences of opiate overdose and acceptability of provision of naloxone kits through ambulance/paramedic emergency services (EMS) and hospital Emergency Departments (ED). Qualitative interviews were conducted with 26 people who had direct experience of opioid use. Participants were recruited at two substance-use treatment centres and a third sector support organisation in three large cities in the United Kingdom. Interviews examined respondents' experiences of opioid use and opioid overdose, access and personal use of naloxone kits, and opinions about kit provision from EMS and hospital ED staff. Interview data were thematically analysed using a constant comparative method. Four key themes were identified during analysis: 1) High levels of overdose experience and knowledge of naloxone and naloxone kits; 2) naloxone kits were perceived as effective and easy to use 3) There were some concerns around the risks of administering naloxone, such as peer aggression during withdrawal. 4) Participants supported much wider personal, family and peer provision of naloxone kits from community support organisations as well as from EMS. Participants felt naloxone kits were an important resource and they wanted increased provision across a range of services including EMS and hospital ED staff as well as community pharmacies and needle exchange centres. Participants wanted naloxone kit provision to be extended to peers, family and friends.